Removal of chromium (III) and cadmium (II) from aqueous solutions - Kocaoba, S; Akcin, G (ELSEVIER SCIENCE BV, 2005)
Chromium and cadmium are toxic heavy metals present in wastewaters from a variety of industries. A strong cation-exchange resin, Amberlite IR 120, was used for the removal of chromium and cadmium. The resin was prepared in two different cationic forms, as Na+ and H+. The opptimum conditions were concentration, pH, stirring time and resin amount. The concentration range was between 2-50 mg/L, pH range between 2-10, stirring time between 5-60 min, and the amount of resin was from 50-1000 mg. Exchange capacities, moisture content and optimum conditions of this resin were determined in a batch system. The stirring speed was 2000 rpm during all of the batch experiments. The initial and final chromium and cadmium amounts were determined by atomic absorption spectrophotometry. The optimum conditions were found to be a concentration of 20 mg/L, pH of 5.5, stirring time of 20 min and 100 mg of resin. The results obtained show that the Amberlite IR 120 strong cation-exchange resin performed well for the removal and recovery of chromium and cadmium.
Keywords: chromium(III); cadmium(II); ion-exchange resins; toxicity; conservative technologies; RECOVERY; WATER; IONS; LEAD; Engineering; Water Resources